Frontispiece: A CO Adsorption Site Change Induced by Copper Substitution in a Ruthenium Catalyst for Enhanced CO Oxidation Activity. Issue 8 (11th February 2019) - Huang, Bo; Kobayashi, Hirokazu; Yamamoto, Tomokazu; Toriyama, Takaaki; Matsumura, Syo; Nishida, Yoshihide; Sato, Katsutoshi; Nagaoka, Katsutoshi; Haneda, Masaaki; Xie, Wei; Nanba, Yusuke; Koyama, Michihisa; et al.
Abstract : Heterogeneous Catalysis . In their Communication on page 2230 ff., H. Kitagawa et al. show that decreasing the CO adsorption energy on Ru atoms by alloying with Cu atoms enhances the CO oxidation activity of Cux Ru1− x nanoparticles.